The role of big data analytics in digital health for COVID-19 prevention and control in Asia - Azmi, Nazmi Ainaa; Mohd Noor, Norhafizah; Mud Shukri, Muhammad Ikhwan; Mahmud, Aidalina; Abdul Manaf, Rosliza (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Big data analytics (BDA) in digital health is critical for gaining the knowledge needed to make decisions, with Asia at the forefront of utilising this technology for the Coronavirus disease 2019 (COVID-19). This review aims to study how BDA was incorporated into digital health in managing the COVID-19 pandemic in six selected Asian countries, discuss its advantages and barriers and recommend measures to improve its adoption. A narrative review was conducted. Online databases were searched to identify all relevant literature on the roles of BDA in digital health for COVID-19 preventive and control measures. The findings showed that these countries had used BDA for contact tracing, quarantine compliance, outbreak prediction, supply rationing, movement control, information update, and symptom monitoring. Compared to conventional approaches, BDA in digital health plays a more efficient role in preventing and controlling COVID-19. It may inspire other countries to adopt this technology in managing the pandemic.